A Heat Exchanger Networks Synthesis Approach Based on Inherent Safety - José A. Inchaurregui-Méndez; Richart Vázquez-Román; José María Ponce-Ortega; M. Sam Mannan (Journal of Chemical Engineering Research Updates, 2015)
An approach to incorporate inherent safety in the synthesis of heat exchanger networks (HEN) based on optimal layouts is given in this work. Hot and cold streams are produced in a set of facilities and some of these facilities may release toxic gas. The geographical allocation where each produced hot and cold stream is then incorporated in the conventional HEN synthesis problem. The number of heat exchangers, area requirement, energy consumption and energy configuration are thus optimally determined. Given are flows, inlet and outlet temperatures for each cold and hot stream as well as sufficient information on cooling and heating services. The annual cost is minimized while allowing for specification of constraints on matches, heat loads and streams splitting. The underlined idea is that inherent safety is achieved when simultaneously producing HEN and optimal facility layouts where risk due to toxic releases is also minimized. The numerical evidence indicates that inclusion of safety layouts with allocations of hot/cold streams can modify conventional HEN synthesis. The resulting model is a highly nonlinear mixed integer program (MINLP).